Efficacy of Siriraj, in-house-developed, frozen gloves for cold therapy reduction of chemotherapy-induced peripheral neuropathy in gynecological cancer patients: randomized controlled trial - Chitkumarn P. (2023)
Objectives: The primary objective of this study was to investigate the efficacy of cold therapy in reducing paclitaxel-based, chemotherapy-induced, peripheral neuropathy (CIPN). The secondary objective was to establish the incidence of CIPN arising from paclitaxel administration. Materials and methods: The study enrolled gynecological cancer patients who were aged over 18 years and receiving chemotherapy which included paclitaxel (175 mg/m2 every 3 weeks). The patients were allocated to control and cold-therapy groups by computer randomization. During paclitaxel administration, frozen gloves developed in-house by Siriraj Hospital were worn—with a cold pack inside—on both hands and both feet by the cold-therapy patients. The CIPN incidence was evaluated by FACT/GOG-Ntx (version 4) at each chemotherapy cycle and at the 1-month follow-up after treatment completion. Results: There were 79 patients (control arm, 40; study arm, 39). The CIPN incidences in the control and cold-therapy groups were 100% and 48.7%, respectively. CIPN was significantly decreased in the intervention group between the first cycle and the 1 month follow-up after chemotherapy cessation (P value < 0.001). Four patients discontinued the cold therapy due to pain, but there were no serious adverse effects due to the therapy. Conclusion: The Siriraj Hospital, in-house-developed, frozen gloves can reduce CIPN effectively as part of cold therapy for paclitaxel-based chemotherapy. The benefits of using the gloves are apparent from the first chemotherapy cycle to the 1-month, post-treatment follow-up assessment.